Graphene films grown on sapphire substrates via solid source molecular beam epitaxy - 唐军 康朝阳 李利民 刘忠良 闫文盛 韦世强 徐彭寿 (Chinese physics B, 2012)
A method for growing graphene on a sapphire substrate by depositing an SiC buffer layer and then annealing at high temperature in solid source molecular beam epitaxy（SSMBE） equipment was presented.The structural and electronic properties of the samples were characterized by reflection high energy diffraction（RHEED）,X-ray diffraction Φ scans,Raman spectroscopy,and near edge X-ray absorption fine structure（NEXAFS） spectroscopy.The results of the RHEED and Φ scan,as well as the Raman spectra,showed that an epitaxial hexagonal α-SiC layer was grown on the sapphire substrate.The results of the Raman and NEXAFS spectra revealed that the graphene films with the AB Bernal stacking structure were formed on the sapphire substrate after annealing.The layer number of the graphene was between four and five,and the thickness of the unreacted SiC layer was about 1-1.5 nm.